Pengaruh NPF, BOPO Dan NOM ,Terhadap Likuiditas Bank Muamalat Indonesia Periode 2017-2021 - Muhamad Ifan Permana; Muhammad Wakhid Musthofa (ITB AAS INDONESIA Surakarta, 2023)
The Purpose of this study was to determine the effect on Non Performing.Financing (NPF), Operating Costs and Operating.Income (BOPO) and Net Operating Margin (NOM) Ratios on Bank Muamalat’s Liquidity for the 2017-2021 period. This Study uses data analisys of Quarterly Financial Reports from 2017-2021 using secondary data. The result of this study indicate that the independent variables NPF, BOPO, and NOM in the t partial test have a significant positive effect on the FDR liquidity devenden and the result of the simultaneous F test have a fairly strong influence at the level of 62 %.